Interleukin‐17A affects extracellular vesicles release and cargo in human keratinocytes. Issue 9 (28th August 2019) - Mangino, Giorgio; Iuliano, Marco; Carlomagno, Silvia; Bernardini, Nicoletta; Rosa, Paolo; Chiantore, Maria Vincenza; Skroza, Nevena; Calogero, Antonella; Potenza, Concetta; Romeo, Giovanna
Abstract: Psoriasis is a chronic inflammatory systemic disease caused by deregulation of the interleukin‐23/‐17 axis that allows the activation of Th17 lymphocytes and the reprogramming of keratinocytes proliferative response, thereby inducing the secretion of cyto‐/chemokines and antimicrobial peptides. Beside cell‐to‐cell contacts and release of cytokines, hormones and second messengers, cells communicate each other through the release of extracellular vesicles containing DNA, RNA, microRNAs and proteins. It has been reported the alteration of extracellular vesicles trafficking in several diseases, but there is scarce evidence of the involvement of extracellular vesicles trafficking in the pathogenesis of psoriasis. The main goal of the study was to characterize the release, the cargo content and the capacity to transfer bioactive molecules of extracellular vesicles produced by keratinocytes following recombinant IL‐17A treatment if compared to untreated keratinocytes. A combined approach of standard ultracentrifugation, RNA isolation and real‐time RT‐PCR techniques was used to characterize extracellular vesicles cargo. Flow cytometry was used to quantitatively and qualitatively analyse extracellular vesicles and to evaluate cell‐to‐cell extracellular vesicles transfer. We report that the treatment of human keratinocytes with IL‐17A significantly modifies the extracellular vesicles cargo and release. Vesicles from IL‐17A‐treated cells display a specific pattern of mRNA which is undid by IL‐17A neutralization. Extracellular vesicles are taken up by acceptor cells irrespective of their content but only those derived from IL‐17A‐treated cells enable recipient cells to express psoriasis‐associated mRNA. The results imply a role of extracellular vesicles in amplifying the pro‐inflammatory cascade induced in keratinocyte by pro‐psoriatic cytokines.